Gene therapy for hearing loss: challenges and the promise of cellular plasticity and epigenetic modulation - Das, Samprita; Manor, Uri (Frontiers in Neurology, 2024)
Hearing loss can profoundly impact an individual’s quality of life, affecting communication, social interactions, and overall well-being. Many people with hearing impairment report feelings of isolation, frustration, and decreased confidence in social settings, which can lead to withdrawal from activities they once enjoyed. Genetics plays a significant role in congenital hearing loss, accounting for approximately half of all cases. While gene therapy holds immense promise for restoring hearing function in cases of hereditary hearing loss (HHL), current methods face certain challenges that must be overcome to successfully develop therapeutic approaches. This review will explore these challenges and offer a perspective on how epigenetic modulation has the potential to address them, potentially revolutionizing the treatment of genetic hearing disorders.